Shoreline Dynamics and Sediment Transport Processes at Chorefto Beach, Pelion: Insights for Sustainable Coastal Management - Balafas, Thomas; Georgiadou, Vasiliki; Billios, Marios; Tsiara, Christina; Kostoula, Maria; Tzima, Anna; Preveniou, Christina; Spiliotopoulos, George; Vasiliades, Lampros; Katsardi, Vanessa (Technical Annals, 2024)
This study explores the geomorphological evolution and shoreline dynamics of Chorefto Beach in Zagora, Pelion, Greece over the period 1945–2023. Combining historical data analysis, field observations, and advanced numerical simulations, the research evaluates natural and anthropogenic influences on sediment transport, erosion, and shoreline stability. Using sediment transport models like the Revised Universal Soil Loss Equation (RUSLE) and the Erosion Potential Method (EPM), the study identifies increased rainfall as a primary driver of sediment deposition. Key findings reveal that sediment contributions from nearby streams, coupled with wave dynamics and wind action, sustain a state of dynamic equilibrium that mitigates erosion risks. Numerical modelling via the MIKE 21/3 coupled system further validates these findings, indicating that even under extreme wind and wave scenarios, erosion remains negligible in critical areas. The results highlight a consistent long-term trend of shoreline accretion, supported by sediment influx from streams and a stable balance of natural forces. The study underscores the importance of integrated coastal zone management strategies to preserve the environmental integrity of Chorefto Beach and promote sustainable coastal development in the face of evolving climatic and anthropogenic pressures. These findings provide critical insights for managing similar vulnerable coastal zones effectively.